What Scientists Say about the Changing Risk Calculation in the Marine Environment under the Harper Government of Canada (2006-2015). (January 2019) - Barnett, Allain J.; Wiber, Melanie G.
This paper examines how the Harper Government of Canada (2006-2015) shut down both debate about threats and research into environmental risk, a strategy that Canadian scientists characterized as the "death of evidence." Based on interviews with scientists who research risks to the marine environment, we explore the shifting relationship between science and the Canadian government by tracing the change in the mode of risk calculation supported by the Harper administration and the impact of this change. Five themes emerged from the interviews: erosion of science research capacity, resulting limitations in understanding risk, declining influence on policy and regulation, redirection of public science funds to support the private sector, and the need to broaden the science knowledge base. The Canadian death of evidence controversy represents a challenge to science and technology studies (STS) scholars who wish to maintain a critical and reflexive perspective on the scientific enterprise without supporting attacks on evidence. While subsequent Canadian governments may simply return science to an unreflexively privileged knowledge status, we view this as equally damaging to broad risk calculation and democratic science. We suggest instead that a broader gathering of matters of concern will always be essential to risk assessment.